Exploring Pre-Service Teachers' Understanding of Join and Separate Word Problems in the Foundation Phase (Grades 1-3). - Cheva, Gift; Mapotse, Tomé Awshar (Profesi Pendidikan Dasar, 2024)
This study explores pre-service teachers’ understanding of different types of join and separate word problems, focusing on their ability to construct word problems from given number sentences. It is a descriptive qualitative study. The participants were second-year pre-service foundation phase teachers taking mathematics learning courses at a public university. Data were collected through number sentence tasks and analysed using a qualitative content analysis procedure. The findings of this study revealed that pre-service teachers demonstrated challenges in correctly formulating word problems from change-unknown and start-unknown scenarios. The findings further reveal that pre-service teachers conflate additive and subtractive reasoning. The findings suggest that pre-service teachers rely on rote memory rather than a deeper understanding of mathematical relations. In addition, the study revealed common misconceptions, particularly in framing “change-unknown” and “result-unknown” problems, where pre-service teachers struggled to model real-life contexts accurately. Findings suggest the need for teacher education programs to focus more explicitly on developing a deep understanding of word problem structure. Initial teacher education programs should include word problem formulation and problem-solving tasks in all five mathematics learning areas, thereby underlining the importance of this research